MENGKOMUNIKASIKAN PERSPEKTIF PEREMPUAN DALAM AL-QUR`AN - Takbir Takbir (Fakultas Dakwah dan Komunikasi, 2015)
God created women and men to complement each other in this kehidpuan wading. When discuss women in the Islamic tradition, namely the restriction of the discussion on the vision of al-Qur`an about women. This is due to several reasons. First, in contrast to the hadith, al-Qur`an is the source of Islamic values that authenticity was never debated. Women are natural reality. How to treat women against him, it's named, or produce social reality. If a husband making out with his wife (woman) does not occur any pornographic event. The new pornography occurs when someone peeping incident, because